PEMANFAATAN LIMBAH SAMPAH RUMAH TANGGA SEBAGAI KOMPOS - Risa Supriningrum; Hayatus Sa'adah; Henny Nurhasnawati (Jurnal Abdi Masyarakat Kita, 2021)
Garbage is a problem that has not been resolved until now. The central and local governments have tried to make regulations on waste management and have disseminated them to the public, but the waste problem still cannot be resolved. Community concern for the environment plays an important role in overcoming this problem. Starting from the smallest scope, namely the family or household to get used to managing waste properly and correctly. Household waste, especially kitchen waste, can be used as compost. The processing of household waste into compost can be done individually or in groups such as at the RT level. This community service aims to provide counseling about the importance of maintaining environmental cleanliness and the use of household kitchen waste as compost. The activity is intended for residents of Jalan Agus Salim RT 18, Sungai Pinang Luar District, Samarinda. The method used is counseling followed by demonstration of composting, pre-test and post-test are also carried out to determine the level of community understanding of this community service activity. This activity was attended by the head of the RT and several residents as representatives of the residents of the RT. The existence of this activity is expected to change people's behavior to be better in managing waste and become a source of income for residents.